Two new species of geckos from Honduras and resurrection of Sphaerodactylus continentalis Werner from the synonymy of Sphaerodactylus millepunctatus Hallowell (Reptilia, Squamata, Gekkonoidea, Sphaerodactylidae) - Mccranie, James R.; Hedges, S. Blair (Zootaxa, 2012)
We performed a morphological and molecular study on various Honduran populations of the Sphaerodactylusmillepunctatus complex. As a result, we resurrect S. continentalis from the synonymy of S. millepunctatus and describetwo new species from the Islas de la Bahía. Our results also suggest the possibility that other cryptic species might occur in our concept of S. continentalis.